2017
DOI: 10.1515/bams-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lexicon- and syntax-based negation detection algorithms using clinical text data

Abstract: Background:Clinical Text Analysis and Knowledge Extraction System (cTAKES) is an open-source natural language processing (NLP) system. In recent development modules of cTAKES, a negation detection (ND) algorithm is used to improve annotation capabilities and simplify automatic identification of negative context in large clinical documents. In this research, the two types of ND algorithms used are lexicon and syntax, which are analyzed using a database made openly available by the National Center for Biomedical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Each grammatical rule is converted into a graph, and then matched against the typed dependency graph using a subgraph matching algorithm. The subgraph matching algorithm is where m is the length of the input, and k is the vertex degree, and must be repeated for every rule [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each grammatical rule is converted into a graph, and then matched against the typed dependency graph using a subgraph matching algorithm. The subgraph matching algorithm is where m is the length of the input, and k is the vertex degree, and must be repeated for every rule [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…One such approach, DEEPEN [ 10 ], operates upon concepts that NegEx determines to be negated. Other dependency-based algorithms make no use of NegEx, such as NegBio, negation-detection, and DepNeg [ [11] , [12] , [13] ], reported to exhibit an improved precision over syntactic approaches. However, an independent assessment showed that ConText maintained its performance over a novel dataset, while the other approaches did not (Goryachev).…”
Section: Introductionmentioning
confidence: 99%
“…This work did not use the instructions given by the journal. Experimental work was published in the Indian Journal of Science and Technology by Manimaran and Velmurugan 17 . The researchers perfectly used the instructions discussed above in this article.…”
Section: Requirements Of Scientific Articlesmentioning
confidence: 99%
“…Two 16 independent reviews comparing rule-based and trained machine learning approaches reported 17 rule-based approaches to be superior in performance [2,3]. Another work reported that machine 18 learning models modestly outperformed rule-based classifiers with out-of-context training, yielding 19 further improvements with in-context training [4]. However, this work compares several machine 20 learning classifiers with one particular implementation of NegEx, that is not used in any of the 21 previous two studies, revealing superior rule-based performance, and does not consider it for 22 additional training in any context (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported as having a similar performance to ConText, with a 112 slightly higher recall. In an independent assessment [19], it was reported to perform extremely well 113 when extended with a richer negation vocabulary [19], outperforming other popular methods. 114…”
mentioning
confidence: 99%